ダイ20ジ ナンキョク チイキ カンソクタイ ヤマト・ベルジカ リョコウ ホウコク - やまと・ベルジカ旅行隊; ヤマト・ベルジカリョコウタイ; Members of the Yamato-Belgica traverse party (1981)
P(論文) 第20次南極地域観測隊(1978-1980)の地質部門は8名の隊を編成し, 1979年10月から1980年2月にかけての115日間やまと山脈ならびにベルジカ山脈への旅行を行い, 各種調査観測を実施した。本報告はこの旅行の経過と調査・観測の概要である。本旅行隊はやまと山脈周辺の裸氷域において約3000個の隕石を新たに発見採集し, さらに, ベルジカ山脈周辺の裸氷においても数個の隕石を採集した。やまと山脈C群, JARE-IVヌナターク(仮称)およびベルジカ山脈の地質調査を完了し, このうちベルジカ山脈については昭和55年度の南極地質図幅シリーズNo.29として出版した。測地作業をベルジカ山脈, 南やまとヌナターク, やまと山脈基岩で実施し, ベルジカ山脈の25000分の1地形図(作業図)を作成した。測地作業の中で基準点観測には測地衛星位置決定装置(JMR)を初めて使用し, 同装置は旅行中の航法にも利用した。SM50大型雪上車の長期旅行への使用は今回が始めてであり, 低温に対する弱点はあったが, 走行性, けん引力等は優秀であった。また, 隕石探査に用いたスノーモビルの機動力は優秀であった。 An 8-man oversnow traverse party of the 20th Japanese Antarctic Research Expedition (JARE-20) made a trip to the Yamato Mountains and the Belgica Mountains from October 13,1979 to January 31,1980. The party collected over 3000 meteorite specimens in the bare ice areas near the Yamato Mountains where about 1000 specimens had hitherto been recovered by JARE. The same party also collected few specimens on the bare ice near the Belgica Mountains located about 200km west of the Yamato Mountains. This report also includes the details of the traverse operations and outlines the scientific activities on geodetic, geological and meteorite research. Logistic aspect of oversnow vehicles, food and cooking, and other gear are described. As a resutlt of the trip, a topographical map and a geological map of the Belgica Mountains have been published in 1981 by the National Institute of Polar Research. departmental bulletin paper